Sovereignty and Necropolitics in the Ideas of the Reconstruction of the Russian World - Budzanowska, Anna (Journal of Public Governance, 2025)
Objective: This article explores the confrontation between Russia and the Western world as a clash between two philosophical visions of sovereignty and international order. Research Design & Methods: Using the qualitative approach based on critical discourse analysis, the article examines state propaganda narratives, public opinion data, and theoretical frameworks of necropolitics, biopower, and sovereign decisionism. Findings: The study reveals that Russia’s political model redefines sovereignty through necropolitical governance, promoting imperial ideology and undermining democratic values in Eastern Europe. Implications / Recommendations: This shift has significant implications for regional governance, weakening democratic institutions and fostering authoritarianism. Contribution / Value Added: The article provides a theoretical contribution to the understanding of sovereignty and power in post-Soviet space, linking propaganda, political philosophy, and systemic transformation. Article classification: theoretical paper JEL classification: Y8, Z00